Financial Management in Categorized Schools the Outstanding School of Muhammadiyah - Hidayatulloh Hidayatulloh; Heri Widodo; Hana Catur Wahyuni (UIN Sunan Gunung Djati, 2022)
The provincial board of Muhammadiyah East Java categorizes three kinds of superior schools: The Outstanding School, The Excellent School, and The Inspiring School of Muhammadiyah. In 2021 there were seven schools categorized as The Outstanding School of Muhammadiyah, one of which is SMA Muhammadiyah 2 Sidoarjo. As the Outstanding School of Muhammadiyah East Java, SMA Muhammadiyah 2 Sidoarjo manages its finances by applying management principles to meet all funding needs for academic and non-academic processes. This study aims to analyze the implementation of financial management at SMA Muhammadiyah 2 Sidoarjo as a school with the category of The Outstanding School of Muhammadiyah. This study uses a qualitative method with a case study design that collects and analyzes financial management data at SMAMDA Sidoarjo. Collecting data using the method of observation, interviews, and documentation. Data analysis was carried out in three stages: data reduction, data exposure, and conclusion examination and verification. The study revealed that the financial management of SMAMDA Sidoarjo runs in accordance with the principles and procedures of financial management of Muhammadiyah schools, including planning, organizing, implementing, controlling, and accountability. In addition to the principles of transparency and accountability, this school also strengthens the principle of budget surplus so that every year the school is able to generate a significant plus balance. In the process of recording, bookkeeping, and reporting using the Sango Professional application system in accordance with financial accounting standards for non-profit institutions (ISAK 35). Financial management in this school shows high transparency and accountability. This can be seen from the achievement of the results of the school financial audit conducted by the Public Accounting Firm in 2021 with the results of an Unqualified Opinion.